The influence of Motivation and Competency toward Agent’s Performance as Sales Distributor at PT Asuransi Allianz Utama Indonesia Semarang Branch - Nuruzzahrotul - Afifah; Siti Nur Barokah; Budi - Prasetya (Politeknik Negeri Semarang, 2020)
This research aims to study the influence of motivation and competency toward agent’s performance at PT Asuransi Allianz Utama Indonesia Semarang Branch.. The methods of data collection used in this study were literature studies, interview and questionnaires with 65 samples. The research analysis shows that both motivation and competency has significant and positive effect on agent’s performance partially and simultaneously. The value of t count in motivation was greater than t table (3.053 > 1.99897) with significant value 0.003 < 0.05 and the value of t count in competence was also greater than t table (4.832 > 1.99897) with significant value of 0.00. The F test stated that both motivation and competency simultaneously had a significant effect on agent’s performance. It was indicated with significant value of 0.000 < 0.05 and the value of F count > F table (73.911 > 3.140). This study concludes motivation and competency is able to contribute on agent’s performance by 69.5% and the remaining of 30.5% is influenced by other variables not examined in this research